Error Analysis in Second Language Acquisition (SLA): Types and Frequencies of Grammatical Errors of Simple Present and Past Tense in the Elicited Written Production Task of Arab EFL Undergraduate Learners - Muftah, Dr. Muneera (Colombian Applied Linguistics Journal, 2023)
This investigation aimed to examine the types and frequencies of grammatical errors of present and past tense and agreement in the elicited written production task (EWPT) of Arab EFL learners. The sample of the study comprised 67 Arab EFL undergraduates selected through a simple random sampling method and subdivided into three proficiency levels. The data collection instrument was the EWPT, which consisted of two passages and a total of 46 test items. The EWPT was collected and the errors committed by the students were identified, classified, and analyzed in frequencies. Then, statistical analysis was performed using SPSS 21. The findings demonstrated two basic types of grammatical errors: error of misformation (EM) and error of omission (EO). Overall results revealed that incorrect use of inflectional morphemes was higher for the EM than for the EO of inflectional morphemes across the three groups of participants. The ungrammatical EM is characterized by the use of incorrect forms, including misusing phonologically similar words, incorrect suffixation, substitution, as well as overgeneralization of be verb forms. Based on these findings, some recommendations and pedagogical implications were proposed, which might assist EFL teachers in developing feasible teaching propositions and policies.